ASSOCIATION BETWEEN PSYCHOLOGICAL DISTRESS AND LATER REPORTS OF HYPERTENSION AMONG ADULTS IN EAST ZIMBABWE. (June 2022) - Shamsuddin, Shehla; Davis, Katherine; Moorhouse, Louisa; Mandizvidza, Phyllis; Dadirai, Tawanda; Nyamukapa, Constance; Gregson, Simon; Chigogora, Sungano
Abstract : Objective: Little is known about the temporal relationship between psychological distress (PD) and hypertension, especially in low-income countries. We assessed the association between PD and later development of hypertension among Zimbabwean adults, and the role of smoking, alcohol consumption and recreational drug use in this relationship. Design and method: Data were taken from the Manicaland Study, an open cohort study in east Zimbabwe. Participants aged 15–54 were surveyed in 2012/2013 and followed-up in 2018/19. At baseline, PD was assessed using the Shona Symptom Questionnaire, a screening tool developed and validated in Shona-speaking countries. Participants self-reported whether they were currently: smokers; took drugs for pleasure; or regularly visited bars and/or consumed over three alcoholic drinks per sitting. At baseline and follow-up, participants reported whether they had ever been diagnosed with hypertension by a doctor/nurse. We selected individuals who did not report hypertension at baseline and used logistic regression to examine associations between baseline PD and hypertension at follow-up, controlling for sociodemographic and economic confounders. We also explored the effect of including binary variables capturing smoking status, drug use and alcohol consumption in the model. Results: 742 participants who completed baseline and follow-up surveys, were not hypertensive at baseline, and had full covariate data, were included. At baseline, 10.4% of these had PD, and at follow-up 17.5% (overall) had developed hypertension. The odds of developing hypertension were 2.01 (95% Confidence Interval = 1.14–3.54) times higher among those with PD at baseline, after adjustment for sociodemographic and economic confounders (Table 1). Introducing smoking status, drug use and alcohol consumption into the model had little effect on our findings (adjusted Odds Ratio, aOR:2.04, 1.16–3.59) and we had little evidence that these behaviours were independently associated with hypertension (aORs:smoking:1.41, 0.40–4.98; alcohol consumption:1.49, 0.61–3.66; drug use:0.49, 0.14–1.75). Conclusions: PD was associated with increased odds of developing hypertension in Manicaland. However, we did not find strong evidence that smoking status, drug use and alcohol consumption contributed to this relationship, which may reflect the low prevalence of these behaviours in our study. The results suggest mental health interventions may be beneficial for reducing hypertension in Zimbabwe.